2019
DOI: 10.1111/obr.12911
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss effects of circuit training interventions: A systematic review and meta‐analysis

Abstract: This meta-analysis aimed to assess the weight loss effects of circuit training interventions in adults. A computerized search was conducted using the Cochrane Central Register of Controlled Trials, PubMed, and EMBASE online databases. The analysis was restricted to randomized controlled trials that evaluated the effects of circuit training interventions on body weight and body mass index in adults aged 18 years or older. Meta-analyses were conducted using the random-effect model to estimate the weighted mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
2
26
0
5
Order By: Relevance
“…Most secondary outcomes also revealed an inverted U-shaped dose-response pattern favoring G2 (Table 1). Decreases of up to 5% in body mass agree with weight loss reported after multimodal training in adults and can meaningfully reduce risks for cardiovascular disease even in normal-weight adults at mid-late life [28]. The pattern of changes in PA indeed raises questions about the IPAQ’s validity because while participants in G2 reported the expected increases in (vigorous) PA in proportion to the 2× per week exercise, that was not the case in G3, reporting in fact less increase in PA than G2 and G1 (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…Most secondary outcomes also revealed an inverted U-shaped dose-response pattern favoring G2 (Table 1). Decreases of up to 5% in body mass agree with weight loss reported after multimodal training in adults and can meaningfully reduce risks for cardiovascular disease even in normal-weight adults at mid-late life [28]. The pattern of changes in PA indeed raises questions about the IPAQ’s validity because while participants in G2 reported the expected increases in (vigorous) PA in proportion to the 2× per week exercise, that was not the case in G3, reporting in fact less increase in PA than G2 and G1 (Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…In this study, circuit training was applied as an exercise intervention method. According to a recent meta-analysis, circuit exercise is known to effectively reduce body weight and BMI in people with obesity [30]. In a 16-week pilot intervention program by our research group, we found that BMI z-score, the primary outcome of the intervention, was significantly decreased in the exercise group with circuit training compared to the baseline after the intervention, but the changes in BMI z-score were not significantly different between groups [28].…”
Section: Resultsmentioning
confidence: 67%
“…The parameters of the exercise protocol were not sufficient to produce meaningful effects on the body composition variables. A series of meta-analysis [58,59] reported that CT improves body composition in obese/ overweight population but the effect varied among the studies. Studies with comparable duration (8-weeks) showed significant improvement in BW, BMI and WHR in obese men [43,60], but no effect on these body composition outcomes in obese women [44].…”
Section: Body Compositionmentioning
confidence: 99%